The effects of a passive exoskeleton on muscle activity and metabolic cost of energy. (2nd January 2020) - Wei, Wei; Wang, Wei; Qu, Zhicheng; Gu, Jihua; Lin, Xichuan; Yue, Chunfeng
ABSTRACT: Nowadays, low back pain has a high incidence during the crowd who work under a long time and repeated stoop condition. Exoskeletons may form a new strategy to reduce the risk of developing low back pain in stressful jobs. A passive exoskeleton device was introduced in this article to apply to the static maintenance of forward bending work, so as to reduce the load of back muscles when wearers work, which plays the role of prevention and subsequent rehabilitation of low back pain. The hypothesis is that these systems would decrease the severity and number of work-related back injuries, while enhancing workers' safety. Through a preliminary analysis and a substantial number of experiments, we have demonstrated the feasibility of our approach to substantially decrease the forces and muscle activities at the L5/S1 location during bending. In the static holding experiment, we find lower muscle activity (by 35%∼61%) and lower metabolic cost of energy (by 22%) when wearing the exoskeleton. The results demonstrate good potential of this passive exoskeleton to reduce muscle activities at the L5/S1 location and metabolic cost of energy. GRAPHICAL ABSTRACT: